2020
DOI: 10.1093/biolinnean/blaa105
|View full text |Cite
|
Sign up to set email alerts
|

An effect size statistical framework for investigating sexual dimorphism in non-avian dinosaurs and other extinct taxa

Abstract: Despite reports of sexual dimorphism in extinct taxa, such claims in non-avian dinosaurs have been rare over the last decade and have often been criticized. Since dimorphism is widespread in sexually reproducing organisms today, under-reporting in the literature might suggest either methodological shortcomings or that this diverse group exhibited highly unusual reproductive biology. Univariate significance testing, especially for bimodality, is ineffective and prone to false negatives. Species recognition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 265 publications
(305 reference statements)
0
18
0
Order By: Relevance
“…Remarkable cases of possible sexual dimorphism have been reported in early-diverging avialans based on soft tissues [e.g. blade-like tail feathers in Confuciusornis (Hou et al, 1996;Martin et al, 1998); but see also Chiappe et al (1999Chiappe et al ( , 2008], whereas convincing evidence based solely on osteology has so far been elusive (Mallon, 2017;Saitta et al, 2020). Among living birds, sexual dimorphism is most commonly expressed by the males, which are larger (an osteological trait) and have more elaborate plumage (a soft-tissue trait) than the females (MĂžller & Cuervo, 1998).…”
Section: (D) Excrescencesmentioning
confidence: 99%
“…Remarkable cases of possible sexual dimorphism have been reported in early-diverging avialans based on soft tissues [e.g. blade-like tail feathers in Confuciusornis (Hou et al, 1996;Martin et al, 1998); but see also Chiappe et al (1999Chiappe et al ( , 2008], whereas convincing evidence based solely on osteology has so far been elusive (Mallon, 2017;Saitta et al, 2020). Among living birds, sexual dimorphism is most commonly expressed by the males, which are larger (an osteological trait) and have more elaborate plumage (a soft-tissue trait) than the females (MĂžller & Cuervo, 1998).…”
Section: (D) Excrescencesmentioning
confidence: 99%
“…We then investigated the resulting dataset using Principal Component Analyses (PCA) and Gaussian Mixture (GM) modelling as clustering analyses. This clustering analysis calculates the number of Gaussian distributions present in a dataset by maximum likelihood estimations and has been demonstrated as a well-suited method for the identification of dimorphism (Godfrey et al, 1993;Dong, 1997;Fabre et al, 2014;Manin et al, 2016;Mallon, 2017;Saitta et al, 2020) Institutional abbreviation: ANG: Angeac-Charente Collection, MusĂ©e d'AngoulĂȘme, AngoulĂȘme, FR…”
Section: Introductionmentioning
confidence: 99%
“…Dimorphism has been reported in every major dinosaur clade and has often been attributed to sex-specific variation (Dodson, 1976; Chapman et al, 1997; Bunce et al, 2003; Padian and Horner, 2011; Knell and Sampson, 2011; Knell et al, 2013; Mallon, 2017; Saitta et al, 2020). However, recent studies have demonstrated that most of the documented cases of sexual dimorphism in extinct dinosaurs were most likely biased by ontogenetic changes, taphonomic deformations and small sample sizes, which substantially affect the representativeness of the inter- and intraspecific diversity, and undermine statistical analyses (Griffin and Nesbitt, 2016; Hone and Mallon, 2017; Saitta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Maiasaura bonebed material is compatible with dimorphism in body mass (Saitta et al 2020). However, sexual dimorphism in cranial anatomy has not been confirmed in any ornithischian dinosaur to date (Mallon 2017).…”
Section: Discussionmentioning
confidence: 95%